2002
DOI: 10.1046/j.1468-3083.2002.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron, ferritin, folic acid, and vitamin B12 levels in recurrent aphthous stomatitis

Abstract: We concluded that vitamin B 12 deficiency may be an aetiological factor in recurrent aphthous stomatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
2
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 4 publications
6
72
2
4
Order By: Relevance
“…Vitamin C inhibits division and growth of cell through the production of hydrogen peroxide, which damages the cells probably through an unidentified free radical(s) generation (Maramag et al 1997). It has been shown that Fe, Ca, and vitamins B12 and C were lower (Ogura et al 2001;Piskin et al 2002) and supplementation with vitamin B12 led to marked improvements in patients suffering from RAU initially deficient in vitamin B12.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C inhibits division and growth of cell through the production of hydrogen peroxide, which damages the cells probably through an unidentified free radical(s) generation (Maramag et al 1997). It has been shown that Fe, Ca, and vitamins B12 and C were lower (Ogura et al 2001;Piskin et al 2002) and supplementation with vitamin B12 led to marked improvements in patients suffering from RAU initially deficient in vitamin B12.…”
Section: Discussionmentioning
confidence: 99%
“…In the research conducted by Piskin et al only the serum level of vitamin B12 was statistically lower in patients with aphthous. It was concluded that vitamin B12 deficiency might be involved in etiology of recurrent aphthous stomatitis (12). The results of the research conducted by Kozlak showed that patients with recurrent aphthous stomatitis had an inadequate daily intake of vitamin B12 and folate compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In the current research, as recovery was observed in both interventional groups, one can consider the important role of alternative and systemic treatments in the improvement of aphthous lesions. Many studies have reported cases of nutritional deficiencies in patients with aphthous (12,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…These ulcerations may be indicative of underlying systemic diseases ranging from vitamin deficiency to autoimmunity [3]. There are several studies investigating the role of genetics, stress, hematinic deficiencies, vitamin deficiencies, trauma, microbial agents and autoimmunity in the literature [4][5][6][7][8].…”
Section: Recurrent Aphthous Stomatitis(ras) Is a Disease Which Presentsmentioning
confidence: 99%